Correlation of Impression Removal Force with Elastomeric Impression Material Rigidity and Hardness. Issue 5 (6th February 2013) - Walker, Mary P.; Alderman, Nick; Petrie, Cynthia S.; Melander, Jennifer; McGuire, Jacob
Abstract Purpose Difficult impression removal has been linked to high rigidity and hardness of elastomeric impression materials. In response to this concern, manufacturers have reformulated their materials to reduce rigidity and hardness to decrease removal difficulty; however, the relationship between impression removal and rigidity or hardness has not been evaluated. The purpose of this study was to determine if there is a positive correlation between impression removal difficulty and rigidity or hardness of current elastomeric impression materials. Materials and Methods Light‐ and medium‐body polyether (PE), vinylpolysiloxane (VPS), and hybrid vinyl polyether siloxane (VPES) impression materials were tested (n = 5 for each material/consistency/test method). Rigidity (elastic modulus) was measured via tensile testing of dumbbell‐shaped specimens (Die C, ASTM D412). Shore A hardness was measured using disc specimens according to ASTM D2240–05 test specifications. Impressions were also made of a custom stainless steel model using a custom metal tray that could be attached to a universal tester to measure associated removal force. Within each impression material consistency, one‐factor ANOVA and Tukey's post hoc analyses (α = 0.05) were used to compare rigidity, hardness, and removal force of the three types of impression materials. A Pearson's correlation (α = 0.05) was used to evaluate the association between impression removal force and rigidity or hardness. Results With medium‐body materials, VPS exhibited significantly higher (p ≤ 0.05) rigidity and hardness than VPES or PE, while PE impressions required significantly higher (p ≤ 0.05) removal force than VPS or VPES impressions. With light‐body materials, VPS again demonstrated significantly higher (p ≤ 0.05) hardness than VPES or PE, while the rigidity of the light‐body materials did not significantly differ between materials (p > 0.05); however, just as with the medium‐body materials, light‐body PE impressions required significantly higher (p ≤ 0.05) removal force than VPS or VPES. Moreover, there was no positive correlation (p > 0.05) between impression removal force and rigidity or hardness with either medium‐ or light‐body materials. Conclusions The evidence suggests that high impression material rigidity and hardness are not predictors of impression removal difficulty.